2014
DOI: 10.2478/s11658-014-0199-z
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30b is involved in methylglyoxal-induced epithelial-mesenchymal transition of peritoneal mesothelial cells in rats

Abstract: Epithelial-mesenchymal transition (EMT) of peritoneal mesothelial cells (PMC) is a major contributor to the pathogenesis of peritoneal fibrosis. EMT is at least in part caused by repeated exposure to glucose degradation products (GDPs), such as methylglyoxal (MGO). MiRNA contributes greatly to the EMT of PMCs. In this study, we tried to profile whether differences exist between the peritoneal membrane (PM) miRNA expression seen in control rats and that seen in rats injected intraperitoneally with MGO. We asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 30 publications
1
32
0
1
Order By: Relevance
“…The prolonged expression of these factors during peritoneal inflammation delays the regression of mesothelial cells back to their epithelial phenotype thereby promoting fibrotic changes in the peritoneum. Other factors recently identified to be associated with MMT include MCP-1 ( Lee et al, 2012 ), ROS ( Liu et al, 2012 ), and the small non-coding regulatory microRNAs miR-589 ( Zhang et al, 2012 ), miR-30a ( Zhou et al, 2013 ), miR-30b ( Liu et al, 2014a ), and miR-200c ( Zhang et al, 2013 ).…”
Section: The Mesothelial Cell In Fibrotic Disordersmentioning
confidence: 99%
“…The prolonged expression of these factors during peritoneal inflammation delays the regression of mesothelial cells back to their epithelial phenotype thereby promoting fibrotic changes in the peritoneum. Other factors recently identified to be associated with MMT include MCP-1 ( Lee et al, 2012 ), ROS ( Liu et al, 2012 ), and the small non-coding regulatory microRNAs miR-589 ( Zhang et al, 2012 ), miR-30a ( Zhou et al, 2013 ), miR-30b ( Liu et al, 2014a ), and miR-200c ( Zhang et al, 2013 ).…”
Section: The Mesothelial Cell In Fibrotic Disordersmentioning
confidence: 99%
“…In abnormal conditions, the obstacle of MGO clearing pathway will lead to the gradual accumulation of MGO content, which can not only directly cause damage to various cells in the body, but also induce the mass-generation of advanced glycation end products [3]. In previous studies, miRNAs have been proved to be closely related to the content of MGO, such as miR-30b [18], miR-214 [19], miR -9a-3p [20], etc. In this study, the expression of miR-450a-5p showed a downregulated trend in HUVECs with high-glucose status, which was also decreased with the increase of MGO concentration.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRs) are a class of single-stranded non-coding RNAs with length of approximately [18][19][20][21][22][23] nucleotides, which exert post-transcriptional modification via binding to the 3'untranslated region of target gene, so as to affect the stability and translation of mRNA. It is estimated that miRNAs account for about 1% of the genome of nuclear organisms, and the regulatory range of their target genes covered 30% of all genes [10].…”
mentioning
confidence: 99%
“…A rat EMT model based on repeated exposure to glucose degradation products (GDPs) during 1-2 weeks, using methylglyoxal (MGO), has been investigated by Liu et al [ 29 ]. Total RNA from the peritoneum of rats subjected to this model was analyzed by miRNA array [ 29 ].…”
Section: Mirna-changes During Pd Therapymentioning
confidence: 99%